The self and the other in the constitution of identity: disengaged children and teenagers from the armed conflict (2008)
This paper presents a reflection on the need to understand how the armed conflict affects the processes of constitution of identity on children and teenagers who have taken part in the armed groups in confrontation, and have left them. It is considered that the social problem represented by the direct participation of under-age youngsters in the armed conflict is closely related to the conditions of human and social development of this population and their reference groups. Therefore, the knowledge and the intervention on this situation represents a challenge to the Colombian Social Work.